Uji Organoleptik Dan Kadar Kalsium Es Krim Dengan Penambahan Kulit Pisang Dan Daun Kelor Sebagai Sumber Gizi Alternatif - Yuliana, Yuliana, Dra. Aminah Asngad, M.Si (2016)
Banana peels consist of 18.90 g carbohydrate and 31 mg of calcium per 100 g. The study of ice cream uses milk, banana peel extract and extract of leaves of Moringa. The purpose of the study is to find out the organoleptic properties, levels of calcium, and the speed of melting ice cream banana peel. The method is was experimental research with two factors completely randomized design. Factor 1 banana skin composition : cow's milk K0 = 0 ml : 200 ml, K1 = 100 ml : 100 ml, K2 = 140 ml : 60 ml. Factor 2 extract of leaves of Moringa S1 = 100 ml, S2 = 75 ml, S3 = 50 ml with 3 repetitions. The highest levels of calcium is in the treatment K0S1 (banana skin 0 ml, 200 ml milk, 100 ml Moringa leaves) as much as 2,258%. Treatment K1S3 (banana peels 100 ml, 100 ml milk, 50 ml of Moringa leaves) has a melt speed for 15 minutes 44 seconds. The highest organoleptic test is at treatment K0S1 (banana skin 0 ml, 200 ml milk, 100 ml Moringa leaves) with a green color, rich aroma, taste slightly sweet, slightly thick but coarse texture, acceptance like. Based on the research results, the addition of Moringa leaves in ice cream banana skin affect the high levels of calcium, melt velocity, and organoleptic tests.